PLMItRNA, a database for mitochondrial tRNA genes and tRNAs in photosynthetic eukaryotes - Damiano, Fabrizio (Oxford University Press, 2001)
The PLMItRNA database for mitochondrial tRNA molecules and genes in Viridiplantae (green plants) [Volpetti,V., Gallerani,R., DeBenedetto,C., Liuni,S., Licciulli,F. and Ceci,L.R. (2000) Nucleic Acids Res., 28, 159–162] has been enlarged to include algae. The database now contains 436 genes and 16 tRNA entries relative to 25 higher plants, eight green algae, four red algae (Rhodophytae) and two Stramenopiles. The PLMItRNA database is accessible via the WWW at http://bio-www.ba.cnr.it:8000/PLMItRNA.